Antagonestic Activities of Aspergillus umbrosus for Biological Control - Sood*, Manjulata (Journal of Ecobiotechnology, 2011)
The antagonistic activities of Aspergillus umbrosus against some phytopathogenic & storage fungi was experimented by co-plating, spore suspension, over-lay & food poison techniques. Results with test organisms indicate an inhibition zone of different size, achieved some success to the objective that A. umbrosus can be used as an agent for biological control.